Efficiency and Policy Development Scenario of Household Waste Management in Blitar City - Purnawan, Heri; Meidiana, Christia; Wijaya, I Nyoman Suluh (Jurnal Pembangunan dan Alam Lestari, 2025)
Assessing the efficiency of urban waste management implementation is crucial for evaluating resource allocation and waste management policy development. The rapid progress in waste handling in Blitar City, reaching 97.73% in 2022, has yet to be accompanied by a corresponding reduction in waste, which still stands at 13.42%. This is further reinforced by the strategic environmental issue currently faced by Blitar City, which is the suboptimal reduction of waste from its source to achieve zero waste. This research aims to evaluate household waste management based on assessing household waste management efficiency in Blitar City and to devise scenarios for increasing household waste reduction in Blitar City. The research objectives were achieved using Stochastic Frontier Analysis (SFA) and Path Scenario Analysis. The research findings indicate that waste management efficiency in Blitar City has increased from 2018 (67.6%) to 2022 (95%). Based on the vision, resources, opportunities, and constraints of waste management in Blitar City, scenarios are divided into three levels, where the Pessimistic and Moderate scenarios are unable to achieve the waste reduction vision or target by 2025, while the Optimistic Scenario can earn a 30% waste reduction target by 2025.   Keywords: Efficiency, Solid waste management, Waste scenario, Waste